2015
DOI: 10.1186/s12937-015-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different arachidonic acid supplementation on psychomotor development in very preterm infants; a randomized controlled trial

Abstract: Background & aimsNutritional supplementation with polyunsaturated fatty acids is important in preterm infants neurodevelopment, but it is not known if the omega-6/omega-3 ratio affects this process. This study was designed to determine the effects of a balanced contribution of arachidonic acid in very preterm newborns fed with formula milk.MethodsThis was a randomized trial, in which newborns <1500 g and/or <32 weeks gestational age were assigned to one of two groups, based on the milk formula they would recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…Secondly, it is closer to human milk content, which is higher in ARA [31]. Thirdly, we have previous evidence, from a randomized clinical trial in very preterm neonates, that infants who received formula with an ARA:DHA ratio of 2:1 had higher blood levels of essential fatty acids during the first year of life, and better psychomotor development, compared to those who received 1:1 ratio [32].…”
Section: Discussionmentioning
confidence: 90%
“…Secondly, it is closer to human milk content, which is higher in ARA [31]. Thirdly, we have previous evidence, from a randomized clinical trial in very preterm neonates, that infants who received formula with an ARA:DHA ratio of 2:1 had higher blood levels of essential fatty acids during the first year of life, and better psychomotor development, compared to those who received 1:1 ratio [32].…”
Section: Discussionmentioning
confidence: 90%
“…Alshweki et al reported that preterm infants receiving a combined ARA and DHA-supplemented preterm infant formula at a 2:1 ratio scored 9 points higher in the Brunet Lezine test for psychomotor development at 24 months of age as compared to preterm infants receiving a similar formula but only supplemented at a 1:1 ratio [71]. At 12 months of age, the infant plasma fatty acyl distribution demonstrated significantly higher ARA levels.…”
Section: Advances In Arachidonic Acid Function: Infant Requirementsmentioning
confidence: 99%
“…In our review, results from 13 randomized controlled trials (RCTs) of LCPUFA intervention for preterm infants that have reported neurodevelopmental outcomes are presented ( Table 1). We discuss the trials included in the Cochrane review (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), as well as two trials that compared formulas with different ratios of LCPUFA (43)(44)(45)(46), one trial of an LCPUFA supplement added in human milk (47)(48)(49)(50)(51), and two trials with subgroups of preterm infants at higher risk of neurodevelopmental impairment (63,64).…”
Section: Randomized Trials Of Post-natal Supplementation In Preterm Imentioning
confidence: 99%
“…of exclusively breastfed infants (43). Conversely, the DINO trial randomized infants born <33 weeks' gestation to formula with a high DHA content (1%) to normal DHA content (0.3%), with a fixed content of AA (0.4%).…”
Section: Randomized Trials Of Post-natal Supplementation In Preterm Imentioning
confidence: 99%